Anxiety sensitivity and opioid misuse among opioid-using adults with chronic pain. (3rd September 2019) - Rogers, Andrew H.; Kauffman, Brooke Y.; Bakhshaie, Jafar; McHugh, R. Kathryn; Ditre, Joseph W.; Zvolensky, Michael J.
ABSTRACT: Background : The opioid epidemic is a significant public health crisis, and this problem is particularly prevalent among individuals with chronic pain. Accordingly, there is an urgent need for interventions to mitigate the risk for opioid misuse and opioid use disorder among people with pain. Given that mental health problems, specifically anxiety, are common among people who misuse opioids, it is important to examine factors that link mental health problems with opioid misuse to ultimately inform the development of novel interventions. Anxiety sensitivity, a transdiagnostic vulnerability factor defined as the fear of anxiety-related physical sensations, may be one important mechanism in elevated opioid misuse among persons with chronic pain. Objective : Therefore, the current cross-sectional study examined anxiety sensitivity (and construct sub-facets) as a predictor of opioid misuse among adults with chronic pain. Method : Adults reporting chronic pain and prescription opioid use completed an online survey. Results : Anxiety sensitivity was associated with multiple aspects of opioid misuse, including current opioid misuse, severity of opioid dependence, and number of opioids used to get high. The magnitude of effects ranged from medium to large. Associations between anxiety sensitivity and opioid misuse were observed over and above the variance accounted for by age, sex, income, education, perceived health, and pain severity. Conclusion : These findings suggest that anxiety sensitivity may be an important treatment target among adults with chronic pain who misuse opioids. Future research should continue to explore the explanatory relevance of anxiety sensitivity in opioid misuse among individuals with chronic pain.